Originality of student's exercises - Mateljan, Vladimir (Array, 2009)
The paper proposes a method for verification of originality of student's exercises. By analysing folder structure and file contents of all students and by comparing them using a hash algorithm, method calculate and displays their similarity. The method can be used for comparison of text files only, and shows the best result when analysing files containing programming code. The method can be used to discover the students that have copied the part or the whole exercise from their colleagues.